CSIR-NET General Aptitude - A New Outlook - Christy Varghese (Lilly Publishing House Changanacherry, 2016)
Third Edition of best seller CSIR - NET General Aptitude - A New Outlook; Includes 14 previous question papers and their detailed solution; 70+ illustrative examples, 150+ practice questions along with chapterwise theory; Accompanied by the exclusive Android app for CSIR-NET General Aptitude; Recommended book for Part A in 15+ prominent coaching centres across the country
Detailed solution of December 2015 Question Paper included
Keywords: Competitive Exam -- General Aptitude